Pengembangan Dan Pengelolaan Fasilitas Objek Wisata Pemandian Alam Kecamatan Namorambe - Darmayanti Ompusunggu; Cece Cece (CIVITAS: Jurnal Studi Manajemen, 2022)
the purpose of ths research is that namorambe natural baths are widely enjoyed bylocal tourists alone but has not been visited by foreign tourists. Though the potential of naturalbeauty is also no less far from tourist attractions in other areas. It is often unable to receivevisitors anymore because the capacity of the gazebo is no longer available. Many groups ofemployees and families come to visit Namorambe nature baths until mat rentals and cottagesexceed availability. The type of research conducted in this study is qualitative research. The datacollection technique in this study used interviews. Based on the results of research on theconstruction of souvenir stalls and restaurants at tourist attraction sites and road repairinfrastructure leading to the location, it is necessary to intervene by the government and findinterested investors. Existing facilities now need to be kept clean and the role of the governmentto conduct counseling and training is needed.